2019
DOI: 10.1083/jcb.201808119
|View full text |Cite
|
Sign up to set email alerts
|

Mdm1 maintains endoplasmic reticulum homeostasis by spatially regulating lipid droplet biogenesis

Abstract: Lipid droplets (LDs) serve as cytoplasmic reservoirs for energy-rich fatty acids (FAs) stored in the form of triacylglycerides (TAGs). During nutrient stress, yeast LDs cluster adjacent to the vacuole/lysosome, but how this LD accumulation is coordinated remains poorly understood. The ER protein Mdm1 is a molecular tether that plays a role in clustering LDs during nutrient depletion, but its mechanism of function remains unknown. Here, we show that Mdm1 associates with LDs through its hydrophobic N-terminal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 59 publications
(78 reference statements)
2
106
0
1
Order By: Relevance
“…Such types of tethers might include diacyl glycerol-O-acyl transferase (DGAT2), which also resides in the ER and has a C-terminal domain that is sufficient for LD interaction (McFie et al, 2018). Recently, several studies have demonstrated that sortin nexin protein 14 (SNX14) and the nuclear protein Mdm1, which are both embedded into the ER, could control formation and turnover of LDs through tethering them to the ER membrane by using an AH on SNX14 (Datta et al, 2019) and a HH motif on Mdm1 (Hariri et al, 2019). Another LD tether is Plin5, whose C-terminus has been shown to be involved in LD-mitochondria contacts (Wang et al, 2011); here, the protein at the LD surface detects the facing membrane, possibly through recognizable features, such as bilayer charges or curvature.…”
Section: Types Of Contact Sites Anchoring Ldsmentioning
confidence: 99%
“…Such types of tethers might include diacyl glycerol-O-acyl transferase (DGAT2), which also resides in the ER and has a C-terminal domain that is sufficient for LD interaction (McFie et al, 2018). Recently, several studies have demonstrated that sortin nexin protein 14 (SNX14) and the nuclear protein Mdm1, which are both embedded into the ER, could control formation and turnover of LDs through tethering them to the ER membrane by using an AH on SNX14 (Datta et al, 2019) and a HH motif on Mdm1 (Hariri et al, 2019). Another LD tether is Plin5, whose C-terminus has been shown to be involved in LD-mitochondria contacts (Wang et al, 2011); here, the protein at the LD surface detects the facing membrane, possibly through recognizable features, such as bilayer charges or curvature.…”
Section: Types Of Contact Sites Anchoring Ldsmentioning
confidence: 99%
“…The resulting FAs need to be re-activated by Faa4, which has been shown to enter the vacuole along with LDs during lipophagy (Wang et al, 2014a;van Zutphen et al, 2014). At the same time, LDs at Nuclear Vacuolar Junctions (NVJs) increase their TAG content using the activated FAs (Hariri et al, 2018(Hariri et al, , 2019. Upon growth resumption from the stationary phase, TAGs stored in LDs are rapidly broken down by LD resident lipases to release and channel DAGs and FAs towards the ER and the vacuole for membrane proliferation (Ganesan et al, 2019;Kurat et al, 2006;Markgraf et al, 2014;Ouahoud et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast cells were grown in YPD medium to mid-log phase (OD600: 0.5 ~ 0.7), before being incubated with 500 ng/ml rapamycin for 4 h. The samples were further processed in the University of Texas Southwestern Electron Microscopy Core Facility using a published protocol (Hariri et al, 2019;Wright, 2000). Basically, cells were fixed with 2 x prefix solution (4% Glutaraldehyde in 0.2 M PIPES, 0.2 M sorbitol, 2 mM MgCl2, 2 mM CaCl2), then stained in uranyl acetate and embedded in Spurr Resin.…”
Section: Conventional Transmission Electron Microscopymentioning
confidence: 99%